Perlindungan Hukum Konsumen atas Barang yang tidak Terdaftar pada Sistem Bisnis Online - Sucen, Sucen (Journal of Law and Policy Transformation, 2019)
One consequence of technological and communication advancement is the business activity that is usually done conventionally has started to shift into the electronic-based system by using a computer network. However, the phenomenon also generates a new problem that is related to the safety standard of products being sold, because many suspected of having no proper approval or license from authorized agency namely the National Agency for Drug and Food Control (NA-DFC). The cosmetic product is one of the examples. The objective of this research to analyze and elaborate legal protection through preventive and repressive means to consumers in the online business system from unregistered items or products in NA-DFC. The research used juridical normative approach, a method  legal research where the analysis itself does not include data or social factors into account. Performing analysis on legal protection for consumers against unregistered products certainly cannot be separated from the Law of Consumer Protection.Result of the research shows preventive legal protection does exist and proven by the existence of Law of the Republic of Indonesia No. 8 of 1999 on Consumer Protection which explicitly states its information that consumers have appropriate protection against the act of deceit, harmful or even any action that may lead to dangerous consequences. The repressive legal protection comes in the form of a maximum of five years imprisonment or a maximum fine of Rp. 2.000.000.000,- for businesses or producers that produce and/or trade items and/or service that does not fulfill or incompatible with pre-determined standards.